Macroeconomics for developing countries - Jha, Raghbendra (London ; New York : Routledge, 1994)
The book presents a comprehensive study of the tools of macroeconomic analysis with particular emphasis on their application in Developing Countries. At the same time, it examines the debate over whether developing economies should have a completely different framework for dealing with macroeconomic problems.
Includes bibliographical references (p.463-485) and index.
lje 31/01/14; oif 10/09/14, 27/04/15
Loans
Keywords: Developing countries -- Economic conditions; Developing countries -- Economic policy; Macroeconomics